Narrative Coherence in Adolescence: Relations With Attachment, Mentalization, and Psychopathology. Issue 3 (3rd May 2020) - Lind, Majse; Vanwoerden, Salome; Penner, Francesca; Sharp, Carla
Abstract: Narrative coherence refers to the overall completeness of the narrative that helps the individual to draw meaning from past events. Research has predominantly focused on developmental trajectories of narrative coherence among typically developing individuals and less research sheds light on narrative coherence in adolescents facing serious psychological difficulties. This study is the first to apply Baerger and McAdams's well-validated coding scheme of narrative coherence to adolescents and to rate narrative coherence based on the content derived from the Child Attachment Interview in the context of attachment security, mentalization, and internalizing and externalizing pathology in 70 inpatient adolescents. Findings emphasized that the coding scheme is applicable for adolescents and attachment narratives. Narrative coherence was negatively correlated with age and no gender differences were found. Higher attachment security and better mentalization both contributed to more coherent narratives. More coherent narratives predicted less externalizing problems, but when controlling for mentalization and attachment security, mentalization was the strongest predictor. The relation between narrative coherence and other social-cognitive constructs is discussed, as well as how poor narrative coherence should be taken into account with respect to psychopathology in adolescence. Finally, the value of this coding scheme to evaluating narrative coherence in adolescence is discussed.